2009
DOI: 10.1016/j.jinorgbio.2008.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Formation of stable and metastable porphyrin- and corrole-iron(IV) complexes and isomerizations to iron(III) macrocycle radical cations

Abstract: Oxidations of three porphyrin-iron(III) complexes (1) with ferric perchlorate, Fe(ClO 4 ) 3 , in acetonitrile solutions at −40 °C gave metastable porphyrin-iron(IV) diperchlorate complexes (2) that isomerized to known iron(III) diperchlorate porphyrin radical cations (3) when the solutions were warmed to room temperature. The 5,10,15,5,10,15,and 2,3,7,8,12,13,17, systems were studied by UV-visible spectroscopy. Low temperature NMR spectroscopy and effective magnetic moment measurements were possible with the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 40 publications
4
27
0
Order By: Relevance
“…Figure 11 shows the UV/Vis spectral change of Fe III (OEP)(4‐NO 2 ‐Hcat) upon oxidation at a constant potential of 1.28 V, in which the Soret band at 386 nm blueshifts to 357 nm with a decrease in intensity and generates a porphyrin dication, [Fe III (OEP)(L)] ++ , which is confirmed by DFT. These spectral changes are characteristic of the presence of a porphyrin π‐cation radical 23. Similar spectral features are also observed during the controlled oxidations of the other complexes reported here.…”
Section: Resultssupporting
confidence: 85%
“…Figure 11 shows the UV/Vis spectral change of Fe III (OEP)(4‐NO 2 ‐Hcat) upon oxidation at a constant potential of 1.28 V, in which the Soret band at 386 nm blueshifts to 357 nm with a decrease in intensity and generates a porphyrin dication, [Fe III (OEP)(L)] ++ , which is confirmed by DFT. These spectral changes are characteristic of the presence of a porphyrin π‐cation radical 23. Similar spectral features are also observed during the controlled oxidations of the other complexes reported here.…”
Section: Resultssupporting
confidence: 85%
“…We not the pure (d xz , d yz ) 3 (d xy ) 1 (d z 2) 1 but the mixed (d xz , d yz ) 3 (d xy ) 1 (d z 2) 1 and (d xy ) 2 (d xz , d yz ) 2 (d z 2) 1 states [40]. We have also reported that [Fe(T i PrP)(PhCHO) 2 ](ClO 4 ) having the axial ligand with lowlying π* orbital adopts much purer (d xz , d yz ) 3 (d xy ) 1 (d z 2) 1 ground state on the basis of the 1 H NMR, 13 C NMR, and EPR spectroscopy although minor contribution from the (d xy ) 2 (d xz , d yz ) 2 (d z 2) 1 state is not negligibly small [41]. The stability of the (d xy ) 2 (d xz , d yz ) 2 (d z 2) 1 ground state in radical cationic Fe(T i PrP•)(ClO 4 ) 2 can be explained in terms of the weaker field-strength of pyrrole nitrogens as compared with those of parent Fe(T i PrP)(ClO 4 ).…”
Section: Resultsmentioning
confidence: 69%
“…To our knowledge, the bis-methoxo complex, [Fe IV (TMP)(OMe) 2 ], is the only example that is well characterized [8]. As for the iron(III) porphyrin radical cations, there are ample examples where the iron(III) ions adopt highspin (S = 5/2), low-spin (S = 1/2), or mixed high-and intermediatespin (S = 3/2, 5/2) states [9][10][11][12][13]. However, there is no example of the iron(III) radical cation where the iron(III) ion adopts a pure intermediate-spin state.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] These pyrrole-based macrocycles have demonstrated impressive synthetic versatility, allowing a fine tunability of their photophysical properties. [4][5][6][7][8][9] In order to improve the harvesting of solar energy in a broad spectral region, it is important to extend the corrole energy absorption across the visible spectrum as much as possible. As already documented, β-pyrrolic modification and extension of the porphyrin π system significantly broadens and redshifts the light absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years corroles have proved to be outstanding light‐harvesting materials, on surfaces or for solar cells . These pyrrole‐based macrocycles have demonstrated impressive synthetic versatility, allowing a fine tunability of their photophysical properties …”
Section: Introductionmentioning
confidence: 99%